2022
DOI: 10.1101/2022.11.11.22282221
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy and safety of therapeutic HPV vaccines to treat CIN 2/CIN 3 lesions: a systematic review and meta-analysis of phase II/III clinical trials

Abstract: Objectives: We aims to assess the efficacy and safety of therapeutic HPV vaccines to treat cervical intraepithelial neoplasia of grade 2 or 3 (CIN2/3). Design: This study is a systematic review and meta-regression that follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses recommendations. Data sources: PubMed, Embase, Web of Science, Global Index Medicus and CENTRAL Cochrane were searched up January 31, 2022. Eligibility criteria: Phase II/III studies reporting the efficacy of therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Non-invasive treatments, like the one examined here, may even used at the point of infection identification prior to diagnosis with CIN2/3 to prevent the progression to from CIN1 to cervical cancer. 27 In this report, we evaluated a novel HPV16 E6/E7 vaccine that contains previously described mutations that inhibit E6 and E7 oncogenic properties or contains only the predicted immunodominant epitopes to increase safety. 25 We demonstrate that mucosal vaccination via an intranasal route in mice was able to reduce tumor burden in a subcutaneous model of HPV tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-invasive treatments, like the one examined here, may even used at the point of infection identification prior to diagnosis with CIN2/3 to prevent the progression to from CIN1 to cervical cancer. 27 In this report, we evaluated a novel HPV16 E6/E7 vaccine that contains previously described mutations that inhibit E6 and E7 oncogenic properties or contains only the predicted immunodominant epitopes to increase safety. 25 We demonstrate that mucosal vaccination via an intranasal route in mice was able to reduce tumor burden in a subcutaneous model of HPV tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A review of different vaccine modalities using variations of HPV16 and HPV18 E6 and E7 as antigens, observed a total overall proportion of regression from CIN2/3 to CIN1 at 0.54 compared a placebo group at 0.27. 27 These numbers represent a meaningful reduction in advancement to cervical cancer, yet room for improvement remains. Studies with an electroporated DNA vaccine candidate suggested that the ability to elicit potent antigen-specific T cell responses correlated with histopathological regression and a reduction in HPV viral DNA detection.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of trial data on effectiveness of a therapeutic vaccine product, we conducted robust exploration around therapeutic vaccine properties, varying effectiveness against productive infections from 50 to 100% and against high-grade lesions from 0 to 50%. An upper-bound of 50% effectiveness at regressing high-grade lesions was imposed based upon modest results of previous therapeutic vaccines that have targeted high-grade lesions and cervical cancer and the expectation that the microenvironment would be less conducive for stimulating a response that would effectively regress high-grade lesions ( 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…These are entirely new medications and similar to currently available vaccines only insofar as they are delivered via injection. A systematic review and meta-analysis completed in 2023 by Ibrahim Khalil et al analyzed the effectiveness of a variety of newly developed therapeutic HPV vaccines in treating cervical cancer [66]. The therapeutic vaccines used in this study were peptide-based, protein-based, viral-vectored, bacterial-vectored, DNA-based, and cell-based vaccines [66].…”
Section: Prospective Therapeutic Use Of Hpv Vaccinesmentioning
confidence: 99%
“…A systematic review and meta-analysis completed in 2023 by Ibrahim Khalil et al analyzed the effectiveness of a variety of newly developed therapeutic HPV vaccines in treating cervical cancer [66]. The therapeutic vaccines used in this study were peptide-based, protein-based, viral-vectored, bacterial-vectored, DNA-based, and cell-based vaccines [66]. The targets of many therapeutic vaccines are E6 and E7 proteins, which are the main proteins that influence infection and carcinogenesis [66].…”
Section: Prospective Therapeutic Use Of Hpv Vaccinesmentioning
confidence: 99%